Guinea-Bissau : Poverty Reduction Strategy Paper-Second Annual Progress Report-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2010)
This Joint Staff Advisory Note reviews progress in the implementation process of the National Poverty Reduction Strategy (NPRS) for Guinea-Bissau during July 2009-10. It is found that Guinea-Bissau has yielded significant results in the first NPRS, and authorities are taking effective measures for better results in the second NPRS. They are also planning a strategy for strengthening governance, promoting economic growth, and reducing poverty and are also requiring international support and a predictable flow of resources for better implementation of the NPRS. On reviewing the same, the IMF approved a three-year arrangement under the Extended Credit Facility (ECF) for 2010-12.